Propiedades Físicas, químicas y Distribución de la materia Orgánica en los Suelos bajo Páramo Zona Centro-Norte del Ecuador - Rodríguez Basantes, Cristian Fernando (2020)
This investigation is to identify the main effects that geology produces on some physical and chemical properties of soils. One hundred forty-four soil samples were taken at a depth of 0 - 30 cm, from 12 geological formations in Ecuador's center-north. The fractionation of the aggregates by size and stability was determined. As well as the organic carbon (CO) associated with each fraction. Also, total organic carbon, coarse particulate organic carbon, fine particulate carbon, and that associated mineral fraction are quantified. It was evident that the soils located in the geological formation Grupo Llanganates (Jcy) present the highest CO content stored, while the Volcanic formation Cotopaxi (Qvx) gives the lowest. The indices of the dynamic model of soil aggregates (DAS) allowed to monitor the processes of aggregation, and disruption by geology. The rate of separation was higher in soils located in the Macuchi Formation (KM). The pH of the grounds did not present significant differences being moderately acidic. Most of the lands tested positive for NaF, and the melanic index less than 1.7 confirming the presence of amorphous allophane-type clays. The paramo of the north-central zone of Ecuador is a very vulnerable ecosystem due to the high anthropic impact; therefore, its conservation and protection must be promoted. It contains labile fractions of C that can be directly returned to the atmosphere and promote climate change and the greenhouse effect.